Oncogenic roles and related mechanisms of the long non-coding RNA MINCR in human cancers - Chao, Ce; Tang, Renzhe; Zhao, Jiamin; Di, Dongmei; Qian, Yongxiang; Wang, Bin (Frontiers in Cell and Developmental Biology, 2023)
Long non-coding RNAs (lncRNAs) play vital roles in regulating epigenetic mechanisms and gene expression levels, and their dysregulation is closely associated with a variety of diseases such as cancer. Several studies have demonstrated that lncRNAs are dysregulated during tumor progression. Recently, the MYC-induced long non-coding RNA MINCR, a newly identified lncRNA, has been demonstrated to act as an oncogene in different cancers, including gallbladder cancer, hepatocellular cancer, colorectal cancer, non-small cell lung cancer, oral squamous cell carcinoma, nasopharyngeal cancer, and glioma. Moreover, MINCR has been reported to act as a biomarker in the prognosis of patients with different cancers. In this review, we summarize and analyze the oncogenic roles of MINCR in a variety of human cancers in terms of its clinical significance, biological functions, cellular activities, and regulatory mechanism. Our analysis of the literature suggests that MINCR has potential as a novel biomarker and therapeutic target in human cancers.